PENDAMPINGAN GURU TPA AR-RAHMAH DENGAN KETERAMPILAN PENGUKURAN TUMBUH DAN KEMBANG SISWA DENGAN METODE SDIDTK - Zainal Munir; Rizki Rinayah Rora; Abdur Rohim; Rizal Kurniawan; Moch. Elvin Nur Avian; Ahmad Muhaimin; Eko Budiawan (JPS : Jurnal Pengabdian Serulingmas, 2022)
Parents are the people who play the most role in achieving optimal growth and development of a child. The role of parents in providing growth and development stimulation is very large. However, the role of the teacher also becomes important, especially when children begin to receive education in kindergarten. In the implementation of teacher assistance with SDIDTK measurement skills. The purpose of community service activities will be capacity building activities or stimulation training and screening for growth and development of preschool children for teachers or clerics at TPA Ar Rahmah Pondok Pesantren Nurul Jadid. Activities are carried out using training methods, discussions or questions and answers, demonstrations through socialization of learning, red-emonstration, mentoring and providing feedback. The results of the activity increase the knowledge of teachers about concepts, stimulation and screening of preschool children's growth and development and teachers can make early detection of growth and development in preschool children appropriately. This good result is expected to be continued with the implementation of early detection of growth and development in preschool children independently by the school, then reported to the health service center. so that the scope of the early detection program for child growth and development increases.